The incidence of cytomegalovirus infection after deceased-donor kidney transplantation from hepatitis-C antibody positive donors to hepatitis-C antibody negative recipients. Issue 1 (1st January 2020) - Yazawa, Masahiko; Fülöp, Tibor; Cseprekal, Orsolya; Talwar, Manish; Balaraman, Vasanthi; Bhalla, Anshul; Azhar, Ambreen; Kovesdy, Csaba P.; Eason, James D.; Molnar, Miklos Z.
Abstract: Background: Deceased-donor kidney transplantation (KT) from hepatitis C (HCV)-infected donors into HCV-uninfected recipients (HCV D+/R−) could become standard care in the near future. However, HCV viral replication by viral transmission might lead to a higher incidence of cytomegalovirus (CMV) infection in these recipients. Methods: A national-registry-based retrospective cohort study was conducted using the Scientific Registry of Transplant Recipients (SRTR) data set. We assessed the incidence of CMV infection in HCV antibody (Ab) negative recipients receiving kidneys from HCV Ab positive (HCVAb D+/R−) and negative (HCVAb D−/R−) donors. The risk of CMV infection was analyzed by Cox regression analysis in a propensity score (PS) matched-cohort of HCVAb D+/R− ( n  = 950) versus HCVAb D−/R− ( n  = 950). Sensitivity analysis was also conducted in the entire cohort ( n  = 181 082). Results: The mean age at baseline was 54 years, 75% were male, and 55% of the patients were African American in PS-matched cohort. Compared to the HCVAb D−/R − patients, recipients with HCVAb D+/R − showed identical probability for the incidence of CMV infection (Hazard Ratio (HR) = 1.00, 95% Confidence Interval (CI): 0.82–1.22). In the sensitivity analysis, compared to the HCVAb D−/R − patients, the HCVAb D+/R − group had a significantly lower risk of CMV infection in the unadjusted analysis (HR = 0.75, 95%CI: 0.65–0.85), while this risk difference disappeared after the adjusted analysis (HR = 0.99, 95%CI: 0.87–1.14). Conclusion: The incidence of CMV infection was similar in recipients who received HCVAb D + and HCVAb D − KT. Further studies are needed to assess this association in KT from HCV nucleic acid positive donors.